Impact of technological turbulence and competitive intensity on employee job performance: The role of workplace digitalization and job crafting - Teng Liu; Cisheng Wu; Kexin Zhang; Manman Ge (PLoS ONE, 2025)
Following the “environment-behavior-performance” paradigm, we aim to examine how the environment influences employee behavior and job performance. We subdivide the environment into the organizational external environment (dynamic environment, including technological turbulence and competitive intensity) and the specific internal work environment (workplace digitalization). Drawing on uncertainty reduction theory and conservation of resources theory, we validate the chain mediating mechanism through which technological turbulence and competitive intensity affect job performance via workplace digitalization and job crafting. The results indicate that technological turbulence has a significant direct positive effect on job performance (b = 0.233, p < .01). Additionally, it indirectly enhances job performance through a chain mediation pathway involving increased workplace digitalization and higher levels of avoidance crafting (b = 0.021, 95% CI [0.001, 0.056]). In contrast, the direct effect of competitive intensity on job performance is not statistically significant (b = 0.146, p = .126); however, it indirectly improves job performance through increased workplace digitalization and both approach crafting (b = 0.121, 95% CI [0.064, 0.205]) and avoidance crafting (b = 0.051, 95% CI [0.022, 0.105]). Overall, this study applies a multi-level chain mediation model to provide empirical evidence that enriches and extends existing research on the effects of dynamic environments on employee job performance.